Simulated source determination of blue ballpoint pen inks using ftir spectroscopy, pearson product moment correlation and principle component analysis - Razak, Nur Diyana Abd (Universiti Sains Malaysia, 2015)
Ballpoint pens are the most common writing implement used to write a document therefore it is not surprising to see their association with criminal cases such as insurance fraud, homicide, drug dealing and kidnapping. The ink deposited by a ballpoint pen is the course of writing a dubious document can reveal useful information about the ballpoint pen. This study uses pair-wise manual comparison, statistical technique of Pearson Product Moment Correlation (PPMC) or simply Pearson’s r and chemometric technique of principle component analysis to determine the ballpoint pen responsible for writing a simulated threatening note. Eleven (11) blue ballpoint pen inks in which one of them was used to write a threatening note were subjected to Fourier Transform Infra Red (FTIR) spectroscopy. The FTIR spectra of the blue ballpoint pen inks were first interrogate using pair- wise i.e. one to one manual comparison followed by PPMC and PCA. Of three techniques employed, only PCA through its principle component score plot had successfully determined the blue ballpoint pen inks responsible for writing the simulated threatening note . This study revealed that combination of FTIR and PCA can be used to determine the original source of ink provided that the reference ink is available.